On the Intertemporal Behavior of the Short-Term Rate of Interest - Sanders, Anthony B.; Unal, Haluk (Journal of Financial and Quantitative Analysis, 1988)
This paper examines the intertemporal behavior of the short-term rate of interest in a mean-reverting model (Vasicek's elastic random walk model). Using the Goldfeld-Quandt switching regressions technique, we show that the mean-reverting model switched regimes three times over the sample period (March 1959 to December 1985) and that two of these switches coincide with the 1979 and 1982 changes in Federal Reserve monetary policy on interest rates. Parameter estimates prove to be unstable over the sample period. There is evidence of slow mean reversion over the entire sample period; yet significant mean-reversion emerges only in the 1979n1982 regime.